OPTIMIZATION OF ORIGINAL VILLAGE INCOME THROUGH BUSINESS MANAGEMENT ASSISTANCE ACTIVITIES FOR VILLAGE-OWNED ENTERPRISES (BUMDES) IN SUMBEREJO VILLAGE - Subagyo Subagyo; Afwan Hariri Agus; Achmad Murdiono (Transpublika Publisher, 2024)
BUMDes is a business entity owned by the village, where the whole or part of the capital is owned by the village through inclusion in a way originating directly from the village's resources. The development of BUMDes aims to strengthen the village's economic institutions and serve as a tool for utilizing the local economy, leveraging various potential types that exist within the village. Sumberejo Village is one of the villages in the Gedangan District, Malang Regency. The methods employed include survey methods, mentoring, and training, observing the village's potential as a creative business unit within society. The training model for BUMDes is designed by combining in-class and outdoor methods, tailored to the participants' needs, providing direct interaction opportunities for participants and BUMDes activists. The target audience for this Community Partnership Program includes BUMDes administrators/organizers and the Sumberejo Village government apparatus in the Sumberejo Subdistrict, Malang Regency. The objectives of this program are to enhance the administrators' abilities in: 1) understanding the method to map the village's asset and develop strategies for achieving village independence, 2) comprehending the method to initiate, determine the type of business, and develop BUMDes as a village-owned business institution, and 3) designing a development strategy for BUMDes to enhance the Village's Original Income. This activity is expected to contribute to the public economic empowerment by adopting BUMDes and providing solutions that can address partner problems effectively.